2022
DOI: 10.1080/22221751.2022.2069516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior vaccination on clinical outcomes of patients with COVID-19

Abstract: Fully vaccinated people remain at risk of Coronavirus Disease 2019 (COVID-19). We examined association between prior vaccination and clinical outcomes in patients with COVID-19. Overall, 387 patients with mild-to-severe COVID-19 were enrolled. Patients were considered fully vaccinated at least 14, 7, and 14 days after receiving the second dose of ChAdOx1 nCoV-19 or mRNA-1273, second dose of BNT162b2, or single dose of Ad26.COV2.S, respectively. The primary outcomes (risk of pneumonia, requirement of supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(37 reference statements)
3
10
0
Order By: Relevance
“…The vaccinated patients with severe COVID-19 infection admitted to ICU presented a higher rate of ischemic heart disease, chronic kidney disease, chronic dialysis, and a higher cumulated number of associated medical conditions. These results are similar to other studies that report a notably higher incidence of comorbidities in vaccinated patients requiring ICU admission [22,[30][31][32][33][34][35] and a weaker association between vaccination and reduced risk of hospitalization for patients with impaired immune status [22]. The high rate of comorbidities might be explained by the exacerbation of coexisting diseases requiring ICU hospitalization or by lower vaccine effectiveness in this population [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…The vaccinated patients with severe COVID-19 infection admitted to ICU presented a higher rate of ischemic heart disease, chronic kidney disease, chronic dialysis, and a higher cumulated number of associated medical conditions. These results are similar to other studies that report a notably higher incidence of comorbidities in vaccinated patients requiring ICU admission [22,[30][31][32][33][34][35] and a weaker association between vaccination and reduced risk of hospitalization for patients with impaired immune status [22]. The high rate of comorbidities might be explained by the exacerbation of coexisting diseases requiring ICU hospitalization or by lower vaccine effectiveness in this population [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, the proportion of patients 0 -17 years admitted due to COVID-19 who were registered with a URI code increased. This is in line with findings among paediatric patients from elsewhere during a period of increasing Omicron dominance [32]. Our results highlight the challenge of using ICD-10 codes for the surveillance of patients hospitalised due to COVID-19, not least the importance of age-and timespecific definitions, and ongoing validation of these to consider temporal changes in patient cohorts and virus characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…Based on their respective definitions, both Norway and Denmark have previously reported differences in the proportion of patients admitted due to COVID-19 over time and by patient characteristics, such as age and vaccination status [10,28]. This is in line with studies reporting temporal changes in patient cohorts and the clinical presentation of hospitalised patients over time [31][32][33][34]. While certain ICD-10 code combinations closely followed the overall trend in new patients admitted with COVID-19 as main cause, the distribution of ICD-10 codes by main cause and sensitivity and specificity of selected code combinations for representing COVID-19 as main cause varied by age and time.…”
Section: Discussionsupporting
confidence: 61%
“…A systematic review of 41 worldwide studies showed that most vaccines prevented people from getting infected, as well as reduced the number of people with severe disease [42]. Results from the study in Korea showed better outcomes of vaccinated patients with mild to severe clinical course [43].…”
Section: Discussionmentioning
confidence: 99%